(untitled) (The Research of Medical Science Review, 2025)
BACKGROUND: Diabetes mellitus is a chronic metabolic condition with an increasing global burden. Its management involves sustained medical care, lifestyle changes, regular monitoring, and treatment of complications. The financial demands of long-term treatment, along with social implications such as reduced work capacity and dependency, can adversely affect adherence to treatment and glycemic control, ultimately influencing clinical outcomes. OBJECTIVE: To explore the relationship between financial burden, social implications, and patient adherence to diabetes management protocols. To assess the correlation of these factors with HbA1c levels and complications of type II diabetes mellitus. METHODS: A cross-sectional study was conducted at the Outpatient Department of Medicine, Khyber Teaching Hospital, Peshawar, Pakistan. A total of 301 patients diagnosed with type II diabetes mellitus were recruited through non-probability convenience sampling. Information was collected using a structured questionnaire, which included data on demographics, socioeconomic status, healthcare expenses, dependency, treatment compliance, HbA1c levels, and diabetes-related complications. Pearson correlation was applied to assess associations between financial burden, social implications, compliance, HbA1c levels, and complications. RESULTS: Financial burden showed a moderate positive correlation with both higher HbA1c (r = 0.42) and increased complications (r = 0.39). Social implications, including dependency and reduced work capacity, were positively correlated with poor glycemic control (r = 0.36). Treatment compliance demonstrated a significant negative correlation with HbA1c (r = -0.45) and complications (r = -0.41), indicating that better compliance was associated with improved outcomes. CONCLUSION: The study highlights that financial stress and social dependency significantly impact diabetes control and complications. Strengthening treatment adherence and addressing the socioeconomic barriers are critical steps in improving outcomes among diabetic patients.